Evaluation of welded joints of dissimilar titanium alloy Ti-5Al-2.5Sn and stainless-steel 304 at different multi-interlayer modes - Muhammad Jawad; Mirza Jahanzaib; Muhammad Ilyas (Materials Research Express, 2022)
Products manufactured by joining titanium and stainless steel are of great attention to the modern-day industries (aerospace and nuclear) due to their several benefits like high strength, low cost, and corrosion resistance. However, it is difficult to join these alloys owing to the formation of TiFe, Ti _2 Fe, and TiFe _2 compounds which damage their mechanical properties. This study aims to evaluate the microstructural and mechanical properties of titanium alloy Ti-5Al-2.5Sn and stainless steel 304 joints. Joining was performed through pulse–gas tungsten arc welding (P-GTAW) by inserting the Nb-Cu multi-interlayer. The effects of welding speed, two multi-interlayer application modes, and arc offset on the microstructure and mechanical properties such as tensile strength and microhardness were investigated. The mechanical properties were evaluated through tensile and hardness tests while microstructural analysis using scanning electron microscopy (SEM) supported by electron dispersive spectroscopy (EDS). The results revealed that sound and high-quality welds were achieved using a multi-interlayer, which inhibited the formation of TiFe, Ti _2 Fe, and TiFe _2 brittle intermetallic compounds (IMCs). Maximum joint strength of 327 MPa was achieved at a welding speed of 200 mm min ^−1 , mode of multi-interlayer (Nb used as a foil and Cu as a wire) at no arc offsetting, whereas a low joint strength was obtained in the multi-interlayer mode (Nb and Cu both as foils), and arc offset towards SS. The SEM and EDS results revealed that a Cu solid solution was obtained in the fusion zone, which improved the tensile strength. Joint fracture surface analysis indicated that ductile fracture was obtained for high-strength and brittle fracture for the low-strength weld. It is evident that high hardness (400 HV) was obtained at a low welding speed (150 mm min ^−1 ) and an arc offset to the stainless steel side owing to the formation of TiCu and Ti _2 Cu phases, as revealed by the x-ray diffraction phase analysis.